In CW625N brass alloys, reducing the dezincification resistance under the standard (ISO 6509), without applying heat treatment - Doğan, Serap Özhan (My University, 2020)
Pirinç alaşımları, diğer malzemeler gibi, korozyonun kaçınılmaz etkisi altındadır. CW625N (CuZn35Pb1) alaşımına kurşunsuz alaşım denir, çünkü bileşiminde maksimum 1,6 Pb içerir. CW625N Sıcak dövme için uygun kurşunsuz pirinç alaşımı, dünya için yeni bir alaşım türüdür.Şehir su hatları, doğalgaz kazan tesisatları, armatürler, termik ve nükleer enerji santrallerinin soğutma hatları gibi alanlarda korozyonun önlenmesi önemli olan pirinç malzemelerin kullanıldığı alanlardır. Sıcak şekillendirme için uygun CW625N (CuZn35Pb1) pirinç alaşımı dünya için yeni bir alaşım türüdür. Geleneksel imalat yönteminde alaşım istenilen compozisyon değerlerinde elde edilmesinden sonra; sıcak dövme ile parçalara istenilen geometrik şekil verilir ve ardından parçalar sakin havada soğutulur. Soğuyan ürünler için son ürün formunu verebilmek için talaşlı işlem uygulanır. Ara aşamada, dövme işleminden sonra alaşımın çinkosuzlaşma direncini arttırmak amacıyla ısıl işlem uygulanır. Ancak bu uygulama çok pahalıdır ve üretim sürecini de oldukça yavaşlatır.Bu çalışmada; yeni bir alaşım tipi CW625N için geleneksel üretim yöntemi kullanmak yerine alternatif bir üretim süreci bulmak amaçlandı. Sıcak dövme ile şekillendirmeye uygun olan bu yeni alaşım için tez kapsamında; üç dövme basıncı (70-80 ve 90Bar) ve üç dövme sıcaklığı (750-765 ve 780°C) altında test parçalarına geometrik şekilleri için sıcak dövme uygulandı. Test numuneleri için dövme sonrası uygulanmak üzere üç tip soğutma yöntemi (sakin havada soğutma, fan ile soğutma ve suda soğutma) belirlendi ve uygulandı. Test parçalarına farklı dövme ve farklı soğutma uygulamalar sonucunda; sakin havada soğutulan ısıl işlem uygulanan grup, sakin havada soğutulan ısıl işlem uygulanmayan grup, fan soğutulan ve ısıl işlem uygulanmayan grup, su ile soğutulan ve ısıl işlem uygulanmayan grup olarak toplamda 4 ana grup oluşturuldu. Her bir parametre uygulaması için üç test parçası yani toplamda 108 adet test numunesi üretildi. Her bir parametre için; numunelerin zamana bağlı soğutma eğrileri, her bir numunenin kimyasal bileşim değerleri, yüzey sertlik değerleri, mikroyapı görüntüleri, mikroyapı içerisindeki tane büyüklük değerleri, çinkosuzlaşma (dezincification) dirençlerine, beta tane büyüklüklerine, beta faz oranlarına, talaşlı imalat aşamasında matkap ile delme işlemi uygulaması ile oluşan delme kuvvetleri, talaş yapıları ve işlenen yüzeye ait pürüzlülük değerleri elde edildi ve incelendi. Bu 4 gruba ek olarak, işlenebilirlik testinden sonra başka bir grup daha eklenmiştir. Isıl işlem grubu için dezinsifikasyon testi sonuçları incelendiğinde; standart kapsamı dışında 11 test numunesi tespit edildi. Bu sebeple çalışmada yeni bir grup oluşturuldu. Çinkosuzlaşma direncini sağlamak için 11 parçaya ikinci kez ısıl işlem uygulandı. Bu yeni gruba 2 kez ısıl işlem uygulanan grup adı verildi. Bu numuneler üzerinde yüzey sertlik ölçümü, mikroyapı incelemesi, çinkosuzlaşma testleri ve işlenebilirlik deneyleri tekrar yapılmıştır. Elde edilen tüm veriler tek tek incelendi.Bu yeni alaşım üzerinde üç önemli konu vardır. Bunlar; optimum dövme parametresini belirlemek, dezinfikasyon direncinin yüksek olmasını (istenen satandart kapsamında elde edilmesi) sağlamak ve alaşımın iyi işlenebilir olmasını sağlamaktır. Bu doğrultuda; yapılan tüm testlerin değerlendirilmesi neticesinde iki ana prosesin tüm sonuçları direk ve en çok etkilediği saptandı. Bunlar; sıcak dövme ile şekillendirilen alaşımın soğutulma yöntemi ve ısıl işlem prosesidir.Isıl işlem pahalı ve nihai ürün için üretim sürecini uzatan bir prosestir. Geleneksel yöntem olan dövme sonrası şekillendirilen ürünlerin sakin havada soğutulması ve sonrasında ısıl işlem uygulaması ile istenen standartlar kapsamında dezinsifikasyon dirençleri elde edilmesi mümkün olmaktadır. Bu çalışmada; sakin havada soğutulan ürünler 2 grup altında incelenmiştir ve sadece bir gruba ısıl işlem uygulanmıştır. Böylelikle farklı sıcaklık ve farklı basınç parametreleri ile oluşturulan 4 grup (her bir grup içerisinde 27 adet test numunesi yer almaktadır) arasında kıyaslamalar ve somut bulgular elde edilmiştir. Sakin havada soğuyan numunelere ısıl işlem uygulanmayan grup içerisinde hangi parametre de şekillendirilmesine (dövülmesine) bağlı olmadan dezinsifikasyon standartı kapsamı dışında kalmıştır. Isıl işlem prosesi ile alaşım içerisindeki dezinfikasyon direnci azaltıcı beta fazını düşürme etkisiyle standart içerisinde kalınmış olup, bu prosesin alaşım üzerindeki direk etkisi saptanmıştır.Alaşımlar içerisinde kurşun miktarı ne kadar yürksek olursa, alaşım o kadar iyi işlenir. Çalışmada kullanılan alaşım adından da anlaşıldığı gibi kurşunsuz bir alaşımdır yani alaşım içerisindeki kurşun miktarı azaltılmış olup standart gereği %1,6 sınırlandırılmıştır. Bu durum; işlenebilirliği direk etkileyen unsurdur. İşlenebilirlik deneyi sonuçları incelendiğinde; ısıl işlem uygulanmayan 3 gruptan biri olan fan ile soğutulan numunelerde istenilen sonuçlar elde edilmiştir. Isıl işlem uygulanan grup numuneleri ile fan ile soğutulan grubun numunelerine ait sonuçlar kıyaslandığında ise talaş yapılarının benzer olduğu görülmüştür. Ancak dezinsifikasyon test sonucuna göre 5. grup oluşturulan ve ikinci kez ısıl işlem uygulanan grubun işlenebilirlik sonuçları (talaş yapısı) istenen yapıda olmamıştır. Sakin havada soğutulan ve bir kez ısıl işlem uygulan grup ile fanla soğutulan grup işlenebilirlik açısından uygunluğu tespit edilmiştir.Tez çalışmasında; geleneksel bir deneysel çalışma yani farklı parametreler sebebiyle toplamda 108 adet test numunesi üzerinde tek tek çalışmalar yapıldı. Her bir deneyde elde edilen bulgular tek tek incelendi. Tüm bu çalışmalara ilaveten taguchi deney tasarımı ve annova varyans analizi uygulandı. Bu istatistiksel analizler sonucu elde edilen bulgular geleneksel çalışma ile elde edilen bulgularla kıyaslandı. Her iki deneysel metot ile yapılan çalışmalar neticesinde bulguların amaçlanan hedefe ulaşıldığı tespit edildi. En iyi dövme parametresi belirlenmiştir. Alaşımda istenilen çinkosuzlaşma direnç değerlerine ve iyi işlenebilirlik sonuçlarına ulaşılmıştır. Yukarıdaki tüm sonuçlara ek olarak, bu çalışmanın en önemli sonucu; geleneksel üretim yöntemi yerine düşük maliyetli alternatif bir yöntem keşfedilmiştir. Gerek dezinsifikasyon test sonuçları gerekse işlenebilirlik test sonuçları incelendiğinde; dövme ile şekillendirilme işlemi sonrası; ürünlerin sakin havada soğutulup ısıl işlem uygulanması (geleneksel yöntem) prosesleri yerine, alaşım ürünlerinin fan ile soğutulması işlemi alternatif bir metot olarak bulunmuştur.

Brass alloys, like other materials, are under the inevitable effect of corrosion. The CW625N (CuZn35Pb1) alloy is called a lead-free alloy because it contains a maximum of 1.6 Pb in its composition. CW625N Lead-free brass alloy, suitable for hot forging, is a new alloy type for the world.Brass materials are using of at the most important areas, which such as city water lines, natural gas boiler installations, armatures, cooling lines of thermal and nuclear power plants. For the all these areas prevention of corrosion is the most important. CW625N (CuZn35Pb1) brass alloy suitable for hot forming is a new type of alloy for the world. In the traditional manufacturing method, after the alloy is obtained at the desired composition values; With hot forging, the parts are given the desired geometric shape and then the parts are cooled in calm air. Machining process is applied to give the final product form for the cooled products. In the intermediate stage, after the forging process, heat treatment is applied to increase the dezincification resistance of the alloy. However, this application is very expensive and also slows down the production process.In this study; it is aimed to find an alternative manufacturing process instead of using the traditional method for a new alloy type CW625N. Three types of cooling methods (cooling in calm air, cooling with fan and cooling in water) were applied for hot forged samples manufactured under the conditions of the three forging pressure (70-80 and 90 Bar) and the three forging temperature (750-765 and 780°C). Three types of cooling methods (calm air cooling, fan cooling and water cooling) were determined and applied for the test samples to be applied after the forging. As a result of different forging and different cooling applications to test pieces; A total of 4 main groups were formed as calm air cooled heat treated group, calm air cooled non heat treated group, fan cooled and non heat treated group, water cooled and non heat treated group. Three test pieces, ie 108 test samples in total, were produced for each parameter application. For each parameter; time-dependent cooling curves of the samples, chemical composition values of each sample, surface hardness values, microstructure images, grain size values in the microstructure, dezincification resistances, beta grain sizes, beta phase ratios, drilling application in the machining stage drilling forces, chip structures and roughness values of the treated surface obtained and examined. In addition to these 4 groups, another group was added after the machinability test. When the dezincification test results are examined for the heat treatment group; out of the standard scope, 11 test samples were detected. For this reason, a new group was created in the study. To ensure dezincification resistance, 11 parts were heat treated for the second time. This new group was given the name of the group, which was heat treated twice. Surface hardness measurement, microstructure examination, dezincification tests and machinability tests were repeated on these samples. All data obtained were examined one by one.There are three important issues on this new alloy. These; to determine the optimum forging parameter, to ensure high dezincification resistance (to be achieved under the desired standard) and to ensure that the alloy is well machinable. In this direction; as a result of the evaluation of all the tests performed, it was found that the two main processes directly and the most affected all the results. These; the method of cooling and heat treatment of the alloy formed by hot forging.Heat treatment is expensive and extends the production process for the final product. it is possible to obtain dezincification resistances within the scope of the required standards by cooling the products formed after forging, which is the traditional method, in calm air and subsequent heat treatment. In this study; products cooled in calm air were examined under 2 groups and only one group was heat treated. thus, comparisons and concrete findings were obtained between 4 groups (27 test samples in each group) formed with different temperature and pressure parameters.The samples which were cooled in calm air were not covered by the dezincification standard, regardless of which parameter was formed (forged) in the group without heat treatment. With the effect of reducing the dezincification resistance reducing beta phase in the alloy by the heat treatment process, the standard effect of this process on the alloy was determined.The higher the amount of lead in the alloys, the better the alloy is processed. As the name of the alloy used in the study is a lead-free alloy, as the name calls, the amount of lead in the alloy is reduced and the standard requirement is limited to 1.6%. This situation; directly affect the machinability. When the machinability test results are examined; The desired results were obtained in the samples cooled by fan which is one of the 3 groups without heat treatment. When the results of heat treated group samples and fan cooled group samples were compared, chip structures were similar. However, according to the results of the dezincification test, the machinability results (chip structure) of the group that formed the 5th group and the second times heat treated group are not in the desired structure. The suitability of the air cooled and one time heat treated group and the fan cooled group are found to be suitable for machinability.In the thesis study; Because of a traditional experimental study, i.e. different parameters, individual studies were carried out on 108 test samples in total. The findings obtained in each experiment were examined one by one. In addition to all these studies, taguchi experiment design and annova variance analysis were applied. The findings obtained from these statistical analyzes were compared with the findings obtained from the traditional study. As a result of the studies carried out with both experimental methods, it was determined that the findings reached the intended target. The best forging parameter has been determined. The desired dezincification resistance values and good machinability results have been achieved in the alloy.In addition to all the above results, the most important result of this study; A low-cost alternative method was discovered instead of the traditional production method. When both the dezincification test results and machinability test results were examined, it is found that; instead of cooling the products in calm air and applying heat treatment (conventional method), cooling of alloy products with fan has been found as an alternative method.
Keywords: Çinkosuzlaşma; Free Lead Brass Alloys; Kurşunsuz Pirinç Alaşımları Dezincification; Makine mühendisliği; Mechanical engineering